1987
DOI: 10.1177/014107688708001210
|View full text |Cite
|
Sign up to set email alerts
|

What Time of Day Should a Urethral Catheter be Removed?

Abstract: Table 1. Postoperative urinary retention and patient presentation for surgery Postoperative course 3 (3.7%) 82 4 (19.0%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…We are able to confi rm that there was no recatheterization at an unsociable hour when the catheter was removed late at night [2,5] ; however, this was necessary with 2 patients who had a ROC performed at 06.00 h.…”
Section: Discussionmentioning
confidence: 76%
“…We are able to confi rm that there was no recatheterization at an unsociable hour when the catheter was removed late at night [2,5] ; however, this was necessary with 2 patients who had a ROC performed at 06.00 h.…”
Section: Discussionmentioning
confidence: 76%
“…However, its implementation was relatively custom-based, hospital policy based and personal preference-dependent, therefore the duration varies markedly. [1][2][3] Routine catheterization up to three days was common after gynaecological surgery. Prolonged catheterization after 24 hrs has minimal benefits in uncomplicated surgery.…”
Section: Introductionmentioning
confidence: 99%
“…3 Urinary retention has also been reported as a common problem following the removal of IUCs 3 and can occur from 7 to 48 h after removal. 4 Although research has focused on the type and maintenance of urinary catheters and techniques for insertion, limited attention has been given to the procedures for their removal, in particular whether the time of day the IUC is removed influences patient outcomes. The insertion, removal and management of IUCs is often undertaken by nurses; however, the decision to remove the IUC frequently rests with the surgeon.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…7 Researchers have also indicated that the time of removal per se does not predispose the patient to urinary retention. 4 Other suggested benefits of IUC removal in the early morning include allowing the patient to rest through the night and adjust to their normal voiding pattern during the day. These reasons have also been proposed to support removal of the IUCs at midnight as people tend to void on waking in the morning.…”
Section: Introduction Backgroundmentioning
confidence: 99%